A study of molybdena catalysts in ethanol oxidation. Part 1. Unsupported and silica‐supported MoO3. Issue 12 (4th September 2021) - Pampararo, Giovanni; Garbarino, Gabriella; Ardoino, Niccolò; Riani, Paola; Busca, Guido
Abstract: Background: Acetaldehyde is a main organic intermediate for manifold chemical products. In the near future, its production using renewable raw materials is rapidly becoming highly desirable. In this paper, investigations on pure and silica‐supported molybdenum oxide (MoO3 ) as catalysts for the ethanol oxidative dehydrogenation process to acetaldehyde are reported. Results: Acicular pure α‐MoO3 crystals and silica‐gel supported MoO3 (1, 5 and 12% wtMoO3 /wtsupport ) were prepared by the thermal decomposition method and by incipient wetness impregnation, respectively. Catalysts were studied and extensively characterized assessing structural, morphological and chemical properties. The samples were tested in ethanol oxidative dehydrogenation through Temperature Programmed Surface Reaction (TPSR) and steady‐state measurements. MoO3 /SiO2 samples were constituted by MoO3 particles weakly interacting with the support, but also by some molybdate species entering the silica framework and significantly modifying the silica morphology. High catalyst acidity limits oxydehydrogenation yield, catalyzing the competitive dehydration reaction to ethylene. Thus, the highest obtained acetaldehyde yield was ≈60%. Molybdenum loss by MoO3 volatilization was found on MoO3 /SiO2 . Conclusion: The produced and characterized catalysts are active, and allow quite a high yield to acetaldehyde. Slight deactivation was observed and also investigated. © 2021 Society of Chemical Industry (SCI).